Beiträge zur Kenntnis der Untersuchungsmerkmale zwischen den Gattungen Ecdyonurus und Heptagenia (Ephemeroptera). - Bogoescu, Constantin; Tabacaru, Ionel (Contributions to Entomology = Beiträge zur Entomologie, 1962)
There is given a new diagnosis of the genera Heptagenia and Ecdyonurus based upon detailed studies of the penis lobes. The European species of the two genera are divided into species groups.